The impact of deferred intake as part of Capacity for Care (C4C) on shelter cat outcomes. Issue 1 (2nd January 2023) - Hobson, Samantha J.; Bateman, Shane; Coe, Jason B.; Oblak, Michelle; Veit, Lisa
ABSTRACT: Capacity for Care (C4C) is a shelter management strategy that is capable of improving the welfare of cats in a shelter's care. Managing shelter intake using intake waitlists and scheduled intake appointments is a key feature of C4C. The purpose of this study was to describe the population of owned cats whose owners contacted the Guelph Humane Society (GHS) to explore the option of relinquishing, and to report outcomes for this population. Data were collected retrospectively from shelter records created by the GHS from July 2017 to June 2018. This study further examined associations between cat outcome and rehoming options under consideration by owners at the initial point of contact with the shelter, cat source, and reason for relinquishment. A greater proportion of cats with veterinary issues reported as the primary reason for potential surrender were kept by their owners compared with being relinquished (p<0.01), rehomed (p<0.01), and having an unknown outcome (p<0.01). A greater proportion of cats whose owners had medical issues were surrendered, compared with being retained in their homes.The large number of cats whose outcomes were unknown suggests a need for future research in order to further understand the outcomes that are occurring for cats whose admission to a shelter are deferred.